Children, Justice, and Femicide: Assessing Victim Rights in Indonesia’s Legal System - Siti Aminah; Elizabeth Kristi Poerwandari; Mariska Putri (Universitas Negeri Semarang, 2025)
The death of a parent profoundly affects a child’s well-being, particularly when caused by homicide committed by a father or the mother’s intimate partner. Research on gender-based killings, or femicide, identifies husbands, boyfriends, and former partners as the most common perpetrators. Yet, children of intimate partner femicide (IPF) victims remain largely invisible in both public discourse and legal protections. This study examines the impacts of IPF on children and evaluates how Indonesia’s legal system supports family recovery, particularly for children who have lost their mothers. Using a qualitative approach, the study draws on literature and an analysis of key Indonesian laws, including the Witness and Victim Protection Act, Criminal Procedure Code, Domestic Violence Elimination Act, Child Protection Act, and Sexual Violence Act. Findings indicate that IPF produces multifaceted harms, including physical and psychological trauma, social challenges, and legal vulnerabilities. Impacts are gendered: girls often assume caregiving roles and mediate between families, while all children experience instability in caregiving, financial insecurity, and increased exposure to trauma. Research on femicide in Indonesia is limited, particularly regarding its effects on children. The study highlights the need for legal reforms to clarify definitions of crime victims and strengthen the rights of family members, ensuring children’s access to comprehensive and sustainable recovery services. Addressing these gaps is crucial for promoting justice and protection for children affected by intimate partner femicide.